Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/ppc.12253
|View full text |Cite
|
Sign up to set email alerts
|

Neglected sexual needs: A qualitative study in Iranian patients with severe mental illness

Abstract: Despite having sexual needs, severe mental illnesses patients do not disclose it due to poor communication between clinician and patients, about sexuality. So, physician had to be pioneer in communicating with them. Therefore, to enhance clinicians' sexual knowledge and effective communication skills with patients, especially those with severe mental illnesses, training is completely necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(33 reference statements)
0
5
0
1
Order By: Relevance
“…The criteria used for the search were as follows: studies published during the previous 10 years and written in Catalan, Spanish, English, German, Portuguese or French. The studies had to have been carried out in Organisation for Economic Co‐operation and Development (OECD) countries, to provide evident data on the experience of sexuality among PLSMI and avoid political, social and/or economic biases that affect the general population and, to a greater extent, people with some type of mental disorder (Raisi et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The criteria used for the search were as follows: studies published during the previous 10 years and written in Catalan, Spanish, English, German, Portuguese or French. The studies had to have been carried out in Organisation for Economic Co‐operation and Development (OECD) countries, to provide evident data on the experience of sexuality among PLSMI and avoid political, social and/or economic biases that affect the general population and, to a greater extent, people with some type of mental disorder (Raisi et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Participants in FGs also reported both paid sexual intercourse and autoerotism. The responses to these behaviors seem to depend on individual staff members' sensitivity and background, consequently resulting in somewhat idiosyncratic and incoherent reactions [29]. In our qualitative research, it is notable that remarks about MHPs' negative responses are more frequent than remarks about their positive ones, suggesting that RPFUs' affective and sexual behaviors are generally judged negatively.…”
Section: Discussionmentioning
confidence: 75%
“…[ 4 6 7 ] SRH is frequently overlooked by clinicians as they concentrate on treating people with psychiatric disorders. [ 9 ] It has been observed that women are reluctant to discuss their sexual needs because their focus will be on concerning psychological symptoms. [ 4 ] The researcher felt that qualitative research is an appropriate initial step to obtain more in-depth information about SRH experiences of WMI because of the complex nature of mental illness.…”
Section: Introductionmentioning
confidence: 99%